Concomitant Use of 1, 550-nm Nonablative Fractional Laser With Low-Dose Isotretinoin for the Treatment of Acne Vulgaris in Asian Patients: A Randomized Split-Face Controlled Study. Issue 9 (September 2018) - Xia, Jun; Hu, Guanglei; Hu, Die; Geng, Songmei; Zeng, Weihui
Abstract : BACKGROUND: Nonablative fractional laser (NAFL) has been shown to improve the appearance of inflammatory acne and acne scars. Isotretinoin is effective for the treatment of moderate-to-severe cases of recalcitrant acne. However, the recommended dose of isotretinoin can have profound effects. OBJECTIVE: To investigate the clinical efficacy and safety of performing NAFL treatment in patients with moderate-to-severe acne vulgaris under treatment with low-dose oral isotretinoin. METHODS AND MATERIALS: Eighteen patients who received 10-mg oral isotretinoin per day completed 3 sessions of NAFL treatment on one half of the face and presented for each scheduled follow-up appointment. RESULTS: Low-dose isotretinoin was effective in managing papules and nodule lesions ( p < .001). Comedo lesions were significantly improved on NAFL-treated half-faces, compared with untreated half-faces ( p < .05) as well as on the appearance of atrophic boxcar scars (superficial boxcar scar, p < .05; deep boxcar scar, p < .01). The most common side effects of oral isotretinoin were xerostomia and cheilitis. The most common discomforts associated with NAFL treatment were mild transient erythema and edema in the treated area. CONCLUSION: The combination of NAFL with low-dose isotretinoin is a safe and effective treatment for moderate-to-severe acne.